Analisis penatausahaan inventarisasi barang milik daerah berdasarkan Permendagri Nomor 47 Tahun 2021 pada Bapenda Kota Manado - Tumilantouw, Kezia Nanseila Wulan; Tinangon, Jantje J.; Walandouw, Stanley Kho (Yayasan Widyantara Nawasena Raharja, 2024)
Inventory is an activity to collect data, record and report the results of data collection on Regional Property (Permendagri 47/2021). Inventory is carried out to provide good data on Regional Property in an effort to create orderly administration and physical order as well as simplify the implementation of management of Regional Property. This research aims to 1) determine the implementation of regional property inventory procedures in the process of data collection, recording and reporting of regional property data collection results at the Regional Development Planning Agency of North Sulawesi Province; 2) know that the implementation of regional property inventory procedures in the process of data collection, recording and reporting of property data collection results is in accordance with Minister of Home Affairs Regulation Number 47 of 2021. This type of research is qualitative research with a descriptive approach. The research results show that the regional property inventory procedures carried out at BAPENDA Manado City are in accordance with Minister of Home Affairs Regulation Number 47 of 2021 concerning Procedures for Implementing Bookkeeping, Inventory and Reporting of Regional Property. However, there are obstacles that often occur, namely problems in inputting data due to the SIMDA BMD application not yet accommodating all of Permendagri No. 47 of 2021 so that it can hamper the process of inputting BMD data.